Eksistensi Hukum Adat Dalam Pembaruan Hukum Pidana Nasional (Studi Putusan Nomor 152 PK/Pdt/2019) - Khoirunnisa, Umni; Zurnetti, Aria (Fakultas Hukum Universitas Andalas, 2024)
The existence of customary law in the reform of national criminal law is an important issue in the context of Indonesia's pluralistic legal system. The Supreme Court decision Number 152 PK/Pdt/2019 provides an example of how customary law is applied in resolving civil disputes involving inheritance and land rights. This study aims to examine the role and challenges of customary law within the national criminal law system, with a focus on the application of customary law in court decisions and its implications for criminal law reform. The research method used is juridical-normative with a legislative approach and case study. Data was collected through analysis of legal literature and relevant documents, which were then analyzed qualitatively. The results show that the application of customary law in the Supreme Court decision Number 152 PK/Pdt/2019 demonstrates the recognition of local legal traditions in resolving disputes, but also faces challenges in harmonizing with more general criminal law principles, such as justice and human rights. The implementation of customary law requires attention to the diversity of existing customs, as well as collaboration between law enforcement agencies, customary communities, and educational institutions. This study highlights the importance of strengthening an inclusive legal system that is responsive to the needs of indigenous communities within the national criminal law context. Keywords : Criminal Law Reform, Customary Law, National Criminal Law, Indonesian Legal System, Legal Pluralism